PENANAMAN NILAI KARAKTER CINTA TANAH AIR: STUDI FENOMENOLOGI DI SD CIPTA DHARMA DENPASAR (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to describe the strategies, obstacles, and efforts to overcome the obstacles in instilling the character values of loving the motherland at SD Cipta Dharma Denpasar. This qualitative research utilizes observation, interview, documentation and literature study to collect the data, involving educators, education staff and students, which are then analyzed interpretively through the steps of: data reduction, data presentation and conclusion drawing. The result shows that the implementation of the character of loving the motherland is carried out in the learning process, which includes: singing the national anthem, folk songs, and providing knowledge related to the cultural diversity and history of the Indonesian state. Outside the classroom, instilling the character values of loving the motherland is carried out through flag ceremonies, extracurricular activities, art performances and other artistic activities. Students are taught to use domestic products, maintain facilities provided by the state, and respecting differences in culture and beliefs. Obstacles in cultivating the character of loving the motherland include: lack of understanding and discipline of students, lack of school cooperation with parents, and environmental conditions of students. Educators and education staff try to become the role models for students, develop extracurricular activities, enforce school regulations, and increase cooperation between teachers and parents to overcome obstacles that occur in the process of cultivating the character values of love for the motherland. Based on the results of this study, it is expected that the parties involved in elementary education should be able to implement the cultivation of loving the motherland character in a synergistic and comprehensive manner in the classroom, outside the classroom and outside of school.